Expression of CD24 in cholangiocarcinoma cells is associated with disease progression and reduced patient survival - Siriporn Keeratichamroen (2018)
Cholangiocarcinoma is frequently found to invade local tissues and metastasize to distal organs. We investigated the expression of CD24 in cholangiocarcinoma samples and its prognostic significance. In addition, the cellular function of CD24 was studied in the RMCCA1 cholangiocarcinoma cell line. High CD24 expression significantly correlated with lymph node metastasis and positive surgical margins in cholangiocarcinoma patients. Univariate and multivariate analyses further demonstrated that CD24 expression was significantly associated with the overall survival of these patients (p=0.007 and p=0.040, respectively). For in vitro studies, the magnetic-activated cell sorting (MACS) system was used to isolate CD24 + and CD24 - cell populations from RMCCA1 cells. CD24 + RMCCA1 cells had increased chemoresistance, adhesion (p=0.004), motility (p < 0.001), migration (p < 0.001) and invasion (p < 0.001) capabilities when compared to CD24 - cells. The matrix metalloproteinase (MMP)-7 was significantly elevated in CD24 + RMCCA1 cells (p=0.01). We found that inhibition of CD24 using siRNA silencing significantly decreased the invasive capacity of RMCCA1 cells. Both clinical and in vitro studies suggest that expression of CD24 is associated with cholangiocarcinoma disease progression. CD24 may thus serve as a new target for directed molecular therapy of cholangiocarcinoma.